Advertising and Cultural Perspective: Trophy Billboard Advertisement in Ilorin as A Paradigm - Abubakar Sidiq Suleman; Ibrahim Olamilekan Quadri; Shuukrat Titilayo Saadu; Kewulere Ma'roof Lawal; Mutiu Adekunle Ganiyu (Ecobankers : Journal of Economy and Banking, 2025)
This study examines the relationship between advertising and the culture of the Trophy Lager beer billboard advertisement at Offa garage area of Ilorin, which generated controversy between the advertiser and the Ilorin Emirate Descendants Progressives Union (IEDPU) in the year 2023. The study's primary purpose was to determine the perception of Ilorin residents about the Trophy Lager beer advertisement. The study was underpinned by reception theory. A survey research method was adopted, and a self-administered questionnaire served as the research instrument for this study. The views of 187 residents of Ilorin were sought on their perception of the Trophy Lager beer billboard advertisement mounted at the Offa garage area of Ilorin in the year 2023. The finding revealed that, although the Trophy billboard advertisement caught the attention of most of the residents of Ilorin, it was against the Islamic cultural relevance for which Ilorin community is known. That respect for local values was highly unfavourable. The study concludes that advertising content should mirror the society through the people's language, religious customs and ideology to motivate the target buyers to purchase the advertised products. The study recommends, among others, that further research should be carried out on the influence of the Trophy Lager beer advertisement on alcohol consumption among Ilorin youth.